SULPHATE POTASIUM EXTRACTION FROM BANANA STEM ASH WITH BLEACHING EARTH WASTE LIQUID - Edahwati, Luluk (Jurnal Teknik Kimia, 2010)
Sulphate potassium is one of the important chemistry compound for industrial at our country, usually for fertilizerindustry. Therefore, necessary done sulphate potassium maker watchfulness from various ingredient that containsulphate potassium compound. Among others with extract banana stem ash. Watchfulness methodology that is withmix banana stem ash with aquadest (20 gram ash/1 water litre) in temperature 100oc during 30 minutes and stirringrotation 300 rpm. Ash extract that got reaction with sulphuric acid found of liquid waste bleaching earth. Bleachingearth with certain rate of flow (5,10,15,20) ml/second is putted into. After achieved steady conditon, process iscontinued up to 15 minutes. Result is analyzed to determine sulphate potassium conversion. Based on watchfulnessresult that done, best condition is got in temperature 60oc with speed emits bleaching earth 10 ml/second, producesulphate potassium degree as big as 20184 mg/litres and conversion that got as big as 88,061%.Keyword : banana stem, bleaching earth